Gamma radiation induced synthesis and characterization of polyvinyl alcohol/polyaniline/CdS nanocomposite - Kharazmi, Alireza (2013)
The polymers/semiconductor nanoparticle composites were prepared from 60 g of polyvinyl alcohol (PVA), 12 g of aniline hydrochloride and different cadmium nitrate concentrations of 0.0462, 0.0924, 0.1386 and 0.186 g and different sulphur thiosulfate concentrations of 0.0372, 0.0744, 0.1116 and 0.15 g respectively in 600- ml deionized water at ambient condition. The aqueous composites were dried several days in a dark room to prepare for composite films which then undergone gamma irradiation with doses up to 50 kGy of Co-60 gamma-rays source at a constant dose rate. As a result, aniline monomers were converted to polyaniline (PANI) and cadmium and sulfur ions were converted to cadmium sulfide (CdS) owing to radiation oxidation and reduction processes respectively. The composites have been transformed into PVA/PANI/CdS nanocomposites and their structural, morphological, optical and electrical properties were characterized by using XRD, FESEM, UV-visible spectroscopy and impedance analyzer, respectively. The formation of crystalline growth of CdS nanoparticles was confirmed by sharp XRD peaks in the 2 range of 10° to 30° which possessed orthorhombic structure with crystal lattice parameter a= 7 Ǻ, b=7.9 Ǻ, c= 10.4 Ǻ and V=567 Ǻ 3 . While, the formation of PVA/PANI composites was confirmed by broad XRD peaks and branch shape FESEM images. The optical absorption spectra of PVA/PANI/CdS nanocomposites revealed characteristic peaks at 316 and 375 nm due to Cl powder and CdS nanoparticles, respectively; and a shoulder at 575 nm due to PANI. The band gap energy decreased from 1.85 eV to 1.65 eV for PANI and increased from 2.55 to 2.70 eV for CdS nanoparticles as the doses increased from 0 to 50 kGy. The dc conductivity of the PVA/PANI/CdS nanocomposites increased from about 4.4x10-7 to 2.4x10-4 S/m owing the creation of polarons in the PANI covalent structure as the doses increased from 0 to 50 kGy.